Evaluating the Quality of Objective and Essay Tests in Cognitive Assessment - Syamsi, Syamsi; Junaidi, Rahmat; Hidayat, Burhanuddin; Syofyandi, Rozi; Julhadi, Julhadi (El-Rusyd, 2025)
Cognitive evaluation instruments are essential tools for systematically and objectively measuring students’ thinking abilities. This study analyzes two primary types of cognitive assessment instruments objective tests and essay tests by evaluating their quality based on established indicators of validity and reliability. The purpose of this research is to examine how effectively these instruments measure cognitive performance across different levels of thinking skills. This study employs a qualitative research method with a content analysis approach, which involves reviewing, selecting, and analyzing scholarly literature, including textbooks, empirical studies, and theoretical documents related to test construction, validity, and reliability. The content analysis reveals that the cognitive domain encompasses mental processes such as problem-solving, reasoning, and the integration of conceptual knowledge. Written cognitive test instruments generally consist of essay tests (restricted and extended response) and objective tests (true–false, multiple-choice, matching, and completion). The findings demonstrate that the overall quality of cognitive evaluation instruments is largely determined by their validity and reliability, which serve as critical benchmarks for ensuring the accuracy and consistency of cognitive measurement.